2012
DOI: 10.1089/gtmb.2012.0191
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Genetic Test of Lactase Persistence in Relation to Milk Consumption in Regional Groups of India

Abstract: Our study indicates that the milk intake in Indians might be influenced by their dietary habits in addition to their ancestral history. An overall correlation, however, between milk consumption and LP genotypes was not observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In addition to these factors, faster and higher production of intermediate and end metabolites by colonic bacteria after lactose hydrolysis have also been reported to be associated with occurrence of LI symptoms (He et al, 2006). Previous study on Indian population showed that À13910C4T polymorphism did not correlate well with milk intake (Baadkar et al, 2012). It was further suggested that low frequency of LI within the LNP genotype group might be responsible for this lack of correlation, since non-symptomatic subjects with low lactase activity might not refrain themselves from drinking milk.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these factors, faster and higher production of intermediate and end metabolites by colonic bacteria after lactose hydrolysis have also been reported to be associated with occurrence of LI symptoms (He et al, 2006). Previous study on Indian population showed that À13910C4T polymorphism did not correlate well with milk intake (Baadkar et al, 2012). It was further suggested that low frequency of LI within the LNP genotype group might be responsible for this lack of correlation, since non-symptomatic subjects with low lactase activity might not refrain themselves from drinking milk.…”
Section: Discussionmentioning
confidence: 99%